Detecção e genotipagem do papilomavírus humano (HPV) em mucosa oral de pacientes do Estado de Sergipe, Brasil - Ribeiro, Mariana Goveia Melo (2014)
Infection with Human Papillomavirus (HPV) is the sexually transmitted viral disease most prevalent in world. The infections can range from asymptomatic establishment to induction of squamous cell carcinomas. It has been discussed the correlation of HPV infection and the development and/or aggravation of lesions in the oral mucosa. The aim of this study was to evaluate the occurrence of HPV and its genotypes in patients with oral lesions and in healthy oral mucosa of users and non-users of drugs in the state of Sergipe, Brazil. Thirty-nine patients aged 2 to 83 years with clinically detectable lesions in the oral mucosa and 106 patients with healthy oral mucosa between 11 and 79 years were evaluated. Samples were collected by exfoliating the oral mucosa. For quality control of DNA extraction beta-globin PCR was performed. HPV DNA was detected using primers MY09/MY11 and GP5+/GP6+. Genotyping was performed by multiplex-PCR with specific primers for HPV types 6, 16 and 18. Our study detected the virus in all types of lesions evaluated. The occurrence of HPV was 76.92% (30/39) in patients with oral lesions. The most common virus type was HPV-6 in 56.67% (17/30), followed by HPV-18 in 26.67% (8/30) and HPV-16 in 6.67% (2/30). Positive results were found in 83.02% (88/106) of patients with healthy oral mucosa. The most common virus type was HPV-6 in 45.45% (40/88), followed by HPV-18 in 35.23% (31/88) and HPV-16 in 4.54% (4/88). Between multiple drug users 86.67% (52/60) were positive and multiple HPV infections were identified in 23.08% (12/52). At |non-users| the occurrence was 78.26% (36/46). A high occurrence of HPV was found in the study, both in oral lesions and in healthy mucosa. Rates of HPV detection in the oral cavity vary markedly in the world and make the relationship between HPV and oral carcinogenesis still controversial. Additional studies to evaluate the role of human papillomavirus in the development of lesions in the oral mucosa are necessary. There are few data available on the frequency of oral HPV infection in Brazilian population and especially among drug users. Other studies on HPV prevalence among drug users are needed for a better understanding of their exposure to the virus and for the development of prevention strategies.